Perbandingan Pola Bentuk Gelombang Karbon Dioksida pada Pernapasan Pasien Asma sebelum dan Sesudah Sembuh - Nindhia, Tjokorda Gde Tirta; Malarvili, M. B.; Hutajulu, Thalitakum; Bhaswara, Nabiel Rafa Angel; Wirastuti, Ni Made Ary Esta Dewi (Prosiding Seminar Nasional Sains dan Teknologi (Senastek), 2023)
Capnography, , is showing promising use in monitoring of airway patency, quality of CPR efforts, and as indicators of abnormal gas exchange. The quantitative characterization of the carbon dioxide (CO2) waveforms has potentially been shown to indicate changes in respiratory airflow, which may be clinical use in discriminating asthmatic severity. The potential clinical application must be evaluated by identifying CO2 waveform indices which change significantly during an acute asthmatic attack. Hence, we aim to assess the CO2 waveform indices (Area and Slope), extracted computationally from three different regions, upward expiratory (4-10 mmHg and 11-15 mmHg) and alveolar phase during pre- and post-treatment using newly developed human respiration, carbon dioxide (CO2) measurement device. We recruited 23 asthmatic patients via convenience sampling method. A signal processing algorithm was applied for automatic segmentation and feature computations, and a paired sample t-test, and Box-whisker plot was performed to know the significant difference of features during the pre- and -post intervention. We found that both the parameters (Area and Slope) were most notable for lower part of expiratory phase (4-10 mmHg, p<0.05), followed by the alveolar period (p<0.05), while upper part of upward expiratory phase (11-15 mmHg) was insignificant for Area (p > 0.05) and significant for slope (p < 0.05). Thus, the inclusion of the features above into the lately developed device may have the potential for the assessment of respiratory distress conditions like asthma in and out of clinical settings as a patient-independent method.